Association between physical activity, depressive symptoms and self-esteem among upper-secondary school students - Lára Margrét Kjartansdóttir 1993- (2018)
Participation in physical activity (PA) is important as it can improve physical and psychological health. The aim of the present study was to analyze the relationship between moderate- to vigorous-intensity PA (MVPA), depressive symptoms and self-esteem among Icelandic adolescents, collectively and also separately between boys and girls. In addition, to examine if self-esteem mediated the relationship between MVPA and depressive symptoms in the total sample and also when controlling for both age and gender. The present study used data from the Icelandic Centre for Social Research and Analysis (ICSRA). The sample consisted of 2008 students, with the mean age of 17.5 years, studying in upper-secondary schools in Iceland. The findings indicate that MVPA was associated with lower levels of depressive symptoms and higher levels of self-esteem with boys, girls and the total sample. Furthermore, self-esteem partially mediates the relationship between MVPA and depressive symptoms in adolescents. There was a complete mediation among girls but a partial among boys and a complete mediation among younger and older girls. Keywords: Physical activity, MVPA, depressive symptoms, self-esteem, gender difference, age difference Hreyfing er afar mikilvæg þar sem hún getur bætt líkamlega og andlega heilsu fólks. Markmið þessarar rannsóknar var að kanna sambandið á milli hreyfingar, af meðal til mikilli ákefð, þunglyndiseinkenna og sjálfsálits, meðal íslenskra unglinga, annars vegar óháð kyni og hins vegar meðal stráka og stelpna. Þar að auki var kannað hvort sjálfsálit miðli sambandinu milli hreyfingar og þunglyndiseinkenna meðal ungmenna, en einnig með tilliti til aldurs og kynjamunar. Notast var við gögn frá Rannsókn og greiningu úr spurningalistanum “Ungt fólk 2016”. Úrtakið innihélt 2008 framhaldsskólanemendur á Íslandi, með meðalaldurinn 17,5 ár. Niðurstöður rannsóknarinnar gáfu til kynna að ástundun hreyfingar, af meðal til mikilli ákefð, dragi úr þunglyndiseinkennum og auki sjálfsálit hjá strákum, stelpum sem og úrtakinu í ...